LDLR gene rearrangements in Czech FH patients likely arise from one mutational event - Konečná, Kateřina; Zapletalová, Petra; Freiberger, Tomáš; Tichý, Lukáš (Lipids in health and disease, 2024)
BACKGROUND: Large deletions and duplications within the low-density lipoprotein receptor (LDLR) gene make up approximately 10% of LDLR pathogenic variants found in Czech patients with familial hypercholesterolemia. The goal of this study was to test the hypothesis that all probands with each rearrangement share identical breakpoints inherited from a common ancestor and to determine the role of Alu repetitive elements in the generation of these rearrangements. METHODS: The breakpoint sequence was determined by PCR amplification and Sanger sequencing. To confirm the breakpoint position, an NGS analysis was performed. Haplotype analysis of common LDLR variants was performed using PCR and Sanger sequencing. RESULTS: The breakpoints of 8 rearrangements within the LDLR gene were analysed, including the four most common LDLR rearrangements in the Czech population (number of probands ranging from 8 to 28), and four less common rearrangements (1-4 probands). Probands with a specific rearrangement shared identical breakpoint positions and haplotypes associated with the rearrangement, suggesting a shared origin from a common ancestor. All breakpoints except for one were located inside an Alu element. In 6 out of 8 breakpoints, there was high homology (≥ 70%) between the two Alu repeats in which the break occurred. CONCLUSIONS: The most common rearrangements of the LDLR gene in the Czech population likely arose from one mutational event. Alu elements likely played a role in the generation of the majority of rearrangements inside the LDLR gene.
Keywords: Low-density lipoprotein receptor; Rearrangements; Gene Rearrangement; mutace; hyperlipoproteinemie typ II; Alu; genová přestavba; Familial hypercholesterolemia; Humans; Mutation; Česká republika; LDL-receptory; Receptors, LDL; lidé; Breakpoints; LDLR; Hyperlipoproteinemia Type II; Czech Republic